Penyuluhan dan Pelatihan Budidaya Kakao bagi Kelompok Tani Pigang Sisan di Kabupaten Sikka - Bolly, Yovita Yasintha; Timung, Andri Permata; Woda, Yanter Wilve Baly; Apelabi, Gabriel Otan; Wahyuni, Yuyun; Anggreani, Yohana; Mutiara, Charly (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The partner in this PKM activity is the Pigang Sisan Farmers Group in Ian Tena village, Kewapante District. The results of a survey conducted by the PKM team found problems faced by partners in carrying out cocoa farming, namely a lack of knowledge and skills of farmers in maintaining garden sanitation, controlling pests and diseases, as well as limited inputs. The aim of this community service activity is to increase farmers' knowledge in cocoa cultivation, the production facilities used, cocoa plant pests, organic fertilizers and pesticides and the importance of maintaining sanitation in cocoa gardens. Apart from targeting knowledge to increase, this activity also targets increasing farmers' skills in making organic fertilizers and pesticides, trapping pests and implementing P3S (pruning, fertilizing, frequent harvesting and sanitation). The extension method is method demonstration extension (Demcar). The application of this method is through counseling and training. From the counseling and training that has been carried out, it was obtained that farmers' knowledge increased by 89.2% and skills by 85.1%. The follow-up plan for the service activities that have been carried out is that there is a need for assistance in post-harvest handling of cocoa fruit and sample gardens.